Discrete Schrödinger equations in the nonperiodic and superlinear cases: homoclinic solutions - Liqian Jia; Jun Chen; Guanwei Chen (Advances in Difference Equations, 2017)
Abstract Using variational methods, we study the existence and multiplicity of homoclinic solutions for a class of discrete Schrödinger equations in infinite m-dimensional lattices with nonlinearities being superlinear at infinity. Our results generalize some existing results in the literature by using some weaker conditions.